Answer:
x = 2 , y = -3
Explanation:
Solve the following system:
{y = 1 - 2 x | (equation 1)
y = x - 5 | (equation 2)
Express the system in standard form:
{2 x + y = 1 | (equation 1)
-x + y = -5 | (equation 2)
Add 1/2 × (equation 1) to equation 2:
{2 x + y = 1 | (equation 1)
0 x+(3 y)/2 = -9/2 | (equation 2)
Multiply equation 2 by 2/3:
{2 x + y = 1 | (equation 1)
0 x+y = -3 | (equation 2)
Subtract equation 2 from equation 1:
{2 x+0 y = 4 | (equation 1)
0 x+y = -3 | (equation 2)
Divide equation 1 by 2:
{x+0 y = 2 | (equation 1)
0 x+y = -3 | (equation 2)
Collect results:
Answer: {x = 2 , y = -3